ЎЗБЕК ТИЛИНИНГ ХОРИЖИЙ ТИЛ СИФАТИДА ЎРГАНИЛИШИ ЖАРАЁНЛАРИ - Қораева, Б.Х. (SCIENCE and SOCIETY, 2021)
Essence and the meaning of this article is dedicated to the problems of learning the Uzbek language as a second language, and also about specific difficulties of this process. Educational programs (curriculum) of learning uzbek language are analyzed in the article as a second foreign language in high educational institutions of the Russian Federation.
Keywords: second foreign language; Uzbek language; culture of speech; stock of words; method of teaching language; vocal activity; speech skills; intercultural communication; practice of the speech communication